Maps of Canberra by suburbs. Phillip 2 - Australia. Department of the Capital Territory (Canberra : Australian Government Publishing Service, 1978)
Map showing land tenure and land usage for Phillip.
Index to suburbs and villages.
Keywords: Land tenure -- Australian Capital Territory -- Phillip -- Maps; Phillip (A.C.T.) -- Maps